All women, all politics: another history of Perú between Manuela Sáenz Aizpuru and Clorinda Matto de Turner - Martínez i Àlvarez, Patrícia-Victòria (2022)
In this text I gather written experiences of politics that happened in Peruvian territory since the independences and throughout the 19th century: I propose the desire for peace, for a nation capable of looking at itself, and the desire for economic and literate freedom for women as keys to the Republic that Manuela Sáenz, Flora Tristán, Juana Manuela Gorriti and Clorinda Matto wanted. While they told and wrote about the need for Peru to be like this, the Republic of caudillos and military, the one of parties and civilistas, well into the next century, would have achieved nothing but the perpetuation of coloniality. I gather here some of the fragments of writings of each of these women to outline their Peru.